Answer:
(f+g)(x)=f(x)+g(x)
=(-3x-5)+(4x-2)
= -3x-5+4x-2. collect like term
= -3x+4x-5-2
= x-7. the final answer
Answer:
C
Step-by-step explanation:
note that sin x = cos(90 - x ) ← Cofunction identity
If x = 36 then 90 - x = 90 - 36 = 54
Hence sin 36° = cos 54° → C
Answer:
3 is the correct answer
Step-by-step explanation:
because
Answer:
4^8
Step-by-step explanation:
If you are multiplying two bases that are the same with different exponents, the exponents get added and the base stays the same:
Therefore, 4^3 * 4^5 = 4^8
Answer:
True
Step-by-step explanation:
It has a common ratio of -1/2
Each term after the first is obtained by multiplying the previous one by -1/2:-
-1/2 * 1/2 = 1/4 ; 1/4 * -1/2 = -1/8 and so on.